Slurry pipeline simulation method - SANDHU; AVTAR S (1982)
Method for simulating the effect upon liquid properties after the passage of a slurry composed of a mixture of solid particulates and liquid through a length of pipeline uses for simulation an apparatus including an outer cylinder closed at both ends. The outer cylinder is horizontally mounted for rotation about its axis and includes a removable cap. Mounted coaxially within the outer cylinder is a relatively small diameter cylindrical pipe. The outer cylinder is made of a material which is substantially inert with respect to a slurry. The outer surface of the cylindrical pipe corresponds to the material for which the actual pipeline is designed. The outer cylinder and the cylindrical pipe are sized so that by rotating the outer cylinder, with a test slurry located between the cylindrical pipe and outer cylinder, for a predetermined time at a chosen speed, the properties of the water in the slurry after passage through the pipeline is simulated.